Implications of COVID-19 for safeguarding in international development research: learning, action and reflection from a research hub. Issue 5 (20th May 2022) - Mansaray, Bintu; Dean, Laura; Tubb, Phil; Josyula, Kunhi Lakshmi; Okoth, Linet; Chumo, Ivy; Waritu, Jane; Klingel, Andrea; Manzoor, Farzana; Aktar, Bachera; Garimella, Surekha; Murthy, Shrutika; et al.
Abstract : COVID-19 brings uncertainties and new precarities for communities and researchers, altering and amplifying relational vulnerabilities (vulnerabilities which emerge from relationships of unequal power and place those less powerful at risk of abuse and violence). Research approaches have changed too, with increasing use of remote data collection methods. These multiple changes necessitate new or adapted safeguarding responses. This practice piece shares practical learnings and resources on safeguarding from the Accountability for Informal Urban Equity hub, which uses participatory action research, aiming to catalyse change in approaches to enhancing accountability and improving the health and well-being of marginalised people living and working in informal urban spaces in Bangladesh, India, Kenya and Sierra Leone. We outline three new challenges that emerged in the context of the pandemic (1): exacerbated relational vulnerabilities and dilemmas for researchers in responding to increased reports of different forms of violence coupled with support services that were limited prior to the pandemic becoming barely functional or non-existent in some research sites, (2) the increased use of virtual and remote research methods, with implications for safeguarding and (3) new stress, anxiety and vulnerabilities experienced by researchers. We then outline our learning and recommended action points for addressing emerging challenges, linking practice to the mnemonic 'the four Rs: recognise, respond, report, refer'. COVID-19 has intensified safeguarding risks. We stress the importance of communities, researchers and co-researchers engaging in dialogue and ongoing discussions of power and positionality, which are important to foster co-learning and co-production of safeguarding processes.